Pro Oracle Collaboration Suite 10g - Watson, John (Apress, 2012)
You don’t have to be an Oracle database administrator or an Oracle Application Server administrator to manage an Oracle Collaboration Suite environment. You don’t have to be a network administrator or a system administrator either. You don’t have to be an expert at managing collaboration services, such as e-mail systems and file servers. But any and all of these skills will help you to manage Oracle Collaboration Suite. The approach I’ve taken in this book is to provide enough information on all these topics to understand their importance and relevance for the use and administration of Oracle Collaboration Suite and to perform some critical tasks; but I have not attempted to teach you all the skills. There are shops with whole bookcases full of material on these matters (one of them written, and several edited, by me). As you become more deeply involved with managing and using Oracle Collaboration Suite, you will have to do further studying in all of the related subjects.